Primary hypertrophic pyloric stenosis in the adult: A case report - (:unkn) unknown (My University, 2002)
A 66-year-old male was admitted with a two-month history of vomiting and weight loss. Endoscopy showed a pyloric obstruction and the patient underwent subtotal gastrectomy with gastro-jejunostomy. The histopathological study of the specimen revealed primary hypertrophic pyloric stenosis without any evidence of duodenal peptic disease. In the adult, this is a rare cause of gastric outlet obstruction of unknown etiology. It is usually recognized by histopathological examination of the specimen after a gastric resection performed to treat gastric outlet obstruction syndrome. However, some endoscopic and radiological signs, such as the cervix sign, or elongation of the pyloric channel, may give clues about the presence of the disease preoperatively. In symptomatic cases, surgery is the preferred treatment modality.
Keywords: Adult gastric outlet obstruction syndrome; Primary hypertrophy; Pyloric stenosis; Pylorus